Pengaruh Kualitas Sistem Informasi, Kesiapan Teknologi, Kompetensi Pengguna Terhadap Penggunaan Sistem Informasi Akuntansi Pada Apotek di Kecamatan Sukalarang - Maharani, Gina Tiara; Martaseli, Evi; Himawan, Irfan Sophan (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the influence of information system quality, technology readiness, and user competence on the use of accounting information systems in pharmacies located in Sukalarang District. The research was motivated by the fact that many pharmacies still rely on manual bookkeeping, whereas accounting information systems can improve efficiency and financial data accuracy. A quantitative approach with a causal research design was employed. Data were collected through questionnaires distributed to 35 pharmacy employees in the region. The data analysis technique used was multiple linear regression, preceded by validity, reliability, and classical assumption tests. The results indicate that both partially and simultaneously, information system quality, technology readiness, and user competence have a positive and significant effect on the use of accounting information systems. The coefficient of determination (R²) value of 84.7% shows that these three independent variables substantially explain the dependent variable. These findings suggest that enhancing system quality, improving technological infrastructure, and strengthening user competence training are essential to ensure effective implementation of accounting information systems in pharmacies.